Upregulation of Salmonella-Induced IL-6 Production in Caco-2 Cells by PJ-34, PARP-1 Inhibitor: Involvement of PI3K, p38 MAPK, ERK, JNK, and NF-κB - Fu-Chen Huang (Hindawi Limited, 2009)
Following Salmonella invasion, intestinal epithelial cells release a distinct array of proinflammatory cytokines. Interleukin (IL)-6 produced by enterocytes may have anti-inflammatory and cell-protective effects, and may counteract some of the injurious effects of sepsis and endotoxemia. Recent studies in a variety of rodent models of experimental colitis by using PJ-34, a potent poly (ADP-ribose) polymerase-1 (PARP-1) inhibitor, support the concept that the marked beneficial effect of PJ-34 can be exploited to treat human inflammatory diseases. The present study was to investigate the effect of PJ-34 on Salmonella-induced enterocyte IL-6 production and its mechanisms. We found that PJ-34 enhanced Salmonella-induced IL-6 production in Caco-2 cells, either secreted protein or mRNA expression. PJ-34 treatment enhanced the activity of NF-κB in Salmonella-infected Caco-2 cells. Besides, the involvement of PJ-34 in up-regulating IL-6 production in S. typhimurium-infected Caco-2 cells might be also through the ERK but not p38 MAPK, JNK or PI3K/Akt pathways, as demonstrated by Western blot of phosphorylated ERK, p38, JNK and Akt proteins. It suggests that PJ-34 may exert its protective effect on intestinal epithelial cells against invasive Salmonella infection by up-regulating IL-6 production through ERK and NF-κB but not P38 MAPK, JNK or PI3K/Akt signal pathways.